2015
DOI: 10.1155/2015/495430
|View full text |Cite
|
Sign up to set email alerts
|

The In Vivo Granulopoietic Response to Dexamethasone Injection Is Abolished in Perforin‐Deficient Mutant Mice and Corrected by Lymphocyte Transfer from Nonsensitized Wild‐Type Donors

Abstract: Exogenously administered glucocorticoids enhance eosinophil and neutrophil granulocyte production from murine bone-marrow. A hematological response dependent on endogenous glucocorticoids underlies bone-marrow eosinophilia induced by trauma or allergic sensitization/challenge. We detected a defect in granulopoiesis in nonsensitized, perforin-deficient mice. In steady-state conditions, perforin- (Pfp-) deficient mice showed significantly decreased bone-marrow and blood eosinophil and neutrophil counts, and colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A systematic screening showed that while wild-type C57BL/6 controls (B6) respond to glucocorticoid administration with bone marrow eosinophilia (thereby mimicking the effect of surgical trauma alone in the EWI model), perforin-deficient knockout mice from the same background lack this response. Reconstitution of the glucocorticoid-induced eosinophilic response is achieved through transfer of splenic T lymphocytes from wild-type (but not from perforin-deficient) donors to perforin-deficient recipients[ 184 ]. Other strains, not restricted to the B6 background, were also shown to lack an eosinophilic response to exogenous and/or endogenous glucocorticoid exposure in the bone marrow (manuscript in preparation).…”
Section: Ewi Model Allows Us To Distinguish Between Neuroendocrine Anmentioning
confidence: 99%
“…A systematic screening showed that while wild-type C57BL/6 controls (B6) respond to glucocorticoid administration with bone marrow eosinophilia (thereby mimicking the effect of surgical trauma alone in the EWI model), perforin-deficient knockout mice from the same background lack this response. Reconstitution of the glucocorticoid-induced eosinophilic response is achieved through transfer of splenic T lymphocytes from wild-type (but not from perforin-deficient) donors to perforin-deficient recipients[ 184 ]. Other strains, not restricted to the B6 background, were also shown to lack an eosinophilic response to exogenous and/or endogenous glucocorticoid exposure in the bone marrow (manuscript in preparation).…”
Section: Ewi Model Allows Us To Distinguish Between Neuroendocrine Anmentioning
confidence: 99%
“…Hence, evidence of a link between GC and bone-marrow eosinophilia was consistently provided by experiments ranging from pharmacological through physiological to immunological settings, which are also summarized in Table 1 . This coherence of effects is to be expected from the well-established fact that GCs, synthetic or natural, act through the same receptor, which is blocked by RU486 (mifepristone[ 45 , 51 - 53 ]).…”
Section: The Central Role Of Glucocorticoids In Extrinsic Regulation mentioning
confidence: 99%
“…Dexamethasone did not induce bone-marrow eosinophilia in vivo in our original study, which used mice of the BALB/c background; however, it did prime bone-marrow for strongly enhanced responses to IL-5 ex vivo over a period of from 24 h[ 51 ] up to 4 wk after injection (manuscript in preparation); more recently, however, an important difference between strains of distinct backgrounds was observed for this drug effect, since bone-marrow eosinophilia was observed in C57BL/6 mice injected with dexamethasone, 24 h after injection, unlike BALB/c controls[ 53 ]. In both BALB/c and C57BL/6 mice, dexamethasone primed bone-marrow for increased eosinophil production in IL-5-stimulated cultures; dexamethasone did not replace IL-5 as a primary eosinopoietic stimulus, but greatly enhanced its effectiveness.…”
Section: The Central Role Of Glucocorticoids In Extrinsic Regulation mentioning
confidence: 99%
See 2 more Smart Citations